2008
DOI: 10.1063/1.2924421
|View full text |Cite
|
Sign up to set email alerts
|

Excitation wavelength dependence of the visible photoluminescence from amorphous ZnO granular films

Abstract: Amorphous ZnO granular films were fabricated by anodizing zinc sheet in 0.5M oxalic acid solution under direct current voltage. The photoluminescence spectrum of the as-anodized sample shows a very broad visible emission band, which can be Gaussian divided into two subbands at 525 and 600nm. Based on their annealing behavior and the growing mechanism of the ZnO films, the two subbands are attributed to optical transitions in oxygen vacancies and oxygen interstitials, respectively. Obvious redshifts of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 30 publications
0
31
0
1
Order By: Relevance
“…Recently, Djurišić et al reported the monotonic quenching and blue‐shift of green emissions of ZnO nanostructures with increasing excitation wavelength, and suggested that the green emissions involve transitions from shallow donor and deep acceptor levels 58. Zhang et al reported the monotonic quenching and red‐shift of green emissions of amorphous ZnO granular films, and attributed the green emission to recombination of electrons trapped in the conduction band and deeply trapped holes in oxygen vacancies 59. Here, the first feature of blue emissions demonstrates that the initial state of the corresponding transitions should be below the conduction band‐edge.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Djurišić et al reported the monotonic quenching and blue‐shift of green emissions of ZnO nanostructures with increasing excitation wavelength, and suggested that the green emissions involve transitions from shallow donor and deep acceptor levels 58. Zhang et al reported the monotonic quenching and red‐shift of green emissions of amorphous ZnO granular films, and attributed the green emission to recombination of electrons trapped in the conduction band and deeply trapped holes in oxygen vacancies 59. Here, the first feature of blue emissions demonstrates that the initial state of the corresponding transitions should be below the conduction band‐edge.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, due to the size induced quantum confinement effect, the band gap for smaller particles will be wider. [27][28][29][30] This quantum confinement effect may be qualitatively understood using Eq. (2) developed for particle-in-a-box model.…”
Section: B Optical Propertiesmentioning
confidence: 99%
“…5 revealed the presence of oxygen related defects in the ZnO crystal lattice. The wide band with two maximums at 580 and 650 nm at the photoluminescence spectra corresponds to irradiative recombination via energy levels in the ZnO band gap associated with oxygen vacancies in ZnO crystal lattice and interstitial oxygen atoms [5,13]. Narrow band with the maximum at 380 nm is also presented on the spectra.…”
Section: Resultsmentioning
confidence: 85%